Aplikasi Pembelajaran Anatomi Organ Dalam Manusia Berbasis Android dengan Teknologi Augmented Reality - Lintang Ardi Avdillah; Agus Suhendar (STMIK Budi Darma, 2023)
Anatomy is the understanding of the structure of organs in the human body. This research explores the application of Augmented Reality (AR) in the context of teaching and understanding human anatomy. By utilizing devices such as smartphones or tablets, users can experience a more interactive approach to learning anatomy. Digital content, including 3D models and contextual information, can be overlaid on real objects or physical anatomy models through AR displays. The use of AR in anatomy education not only enhances student engagement but also enables a profound visualization experience. Users can directly interact with anatomical structures to gain a better understanding. Previously, students learned through manual textbooks, resulting in less captivating and interactive learning experiences. Hence, an anatomy learning application was developed using AR technology to overcome these challenges.The future of AR in anatomy education promises improvements in interactive content development, the incorporation of up-to-date data into 3D models, and the potential for enhanced remote collaboration through AR. By continuously exploring the potential of this technology, education can achieve a more effective and engaging approach to anatomy learning. This research concludes that facilitating learning by allowing students to recognize visualizations of each organ in the human body in 3D is essential. By continually exploring innovations in AR integration, we can enhance students' understanding of human anatomy structures in unprecedented ways.